USM HELPS IUM TO BECOME MORE COMPREHENSIVE - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 11 June 2015 – Universiti Sains Malaysia (USM) will cooperate and help Islamic University of Madinah (IUM) to be more comprehensive with the offering of new courses other than Islamic Studies such as Engineering, Computer Sciences and Sciences following the signing of a Memorandum of Understanding (MoU) held today in USM.